Update on the geographical distribution and prevalence of Aedes aegypti and Aedes albopictus (Diptera: Culicidae), two major arbovirus vectors in Cameroon. - Armel N Tedjou; Basile Kamgang; Aurélie P Yougang; Flobert Njiokou; Charles S Wondji (Public Library of Science (PLoS), 2019)
Introduction Arboviral diseases including dengue are increasingly spreading in the tropical/subtropical world including Africa. Updated knowledge on the distribution and abundance of the major vectors Aedes aegypti and Aedes albopictus constitutes crucial surveillance action to prepare African countries such as Cameroon for potential arbovirus outbreaks. Here, we present a nationwide survey in Cameroon to assess the current geographical distribution and prevalence of both vectors including a genetic diversity profiling of Ae. albopictus (invasive species) using mitochondrial DNA. Methods Immature stages of Aedes were collected between March and August 2017 in 29 localities across Cameroon following north-south and east-west transects. Larvae and pupae were collected from several containers in each location, reared to adult and morphologically identified. Genetic diversity of Ae. albopictus from 16 locations were analysed using Cytochrome Oxidase I gene (COI). Results In total, 30,381 immature stages of Aedes with an average of 646.40±414.21 per location were identified across the country comprising 69.3% of Ae. albopictus and 30.7% of Ae. aegypti. Analysis revealed that Ae. aegypti is still distributed nation widely whereas Ae. albopictus is limited to the southern part, around 6°4'N. However, Ae. albopictus is the most prevalent species in all southern locations where both species are sympatric except in Douala where Ae. aegypti is predominant. This suggests that factors such as climate, vegetation, and building density impact the distribution of both species in Cameroon. Mitochondrial DNA analysis revealed a low genetic diversity in Ae. albopictus populations with a major common haplotype resulting in low haplotype diversity ranging from 0.13 to 0.65 and 0.35 for the total sample. Similarly, low nucleotide diversity was also reported varying from 0.0000 to 0.0017 with an overall index of 0.0008. This low genetic polymorphism is consistent with the recent introduction of Ae. albopictus in Cameroon. Conclusion This updated distribution of arbovirus vectors across Cameroon will help in planning vector control programme against possible outbreak of arbovirus related diseases in the country.